Analyzing the correlation between acute ischemic stroke and triglyceride-glucose index based on ordered logistic regression - Liu He; Rong Li; Lei Wang; Xi Zhu; Qiang Zhou; Zhiyong Yang; Hua Liu (Frontiers in Neurology)
ObjectiveTo investigate the association between insulin resistance, measured by the triglyceride-glucose (TyG) index, and clinical outcomes in patients with acute ischemic stroke who underwent intravenous thrombolysis with alteplase.MethodsThis retrospective study included 165 patients with acute ischemic stroke treated with intravenous alteplase. Insulin resistance was evaluated using the TyG index, and its relationship with the modified Rankin Scale (mRS) scores was analyzed. The analysis was conducted using R software (version R 4.1.3) to evaluate the correlation between the TyG index and functional outcomes at 14, 30, and 90 days post-stroke.ResultsThe study found that each unit increase in the TyG index significantly raised the risk of poor functional outcomes at 14 days (OR 9.86; 95% CI: 3.32–32.21; P < 0.001), 30 days (OR 5.82; 95% CI: 2.08–17.45; P = 0.001), and 90 days (OR 9.79; 95% CI: 3.33–31.66; P < 0.001) following a stroke. Higher TyG index values were associated with worse neurological outcomes. Although male gender, older age, and smoking were also linked to poorer outcomes, these associations did not reach statistical significance.ConclusionThe findings suggest that a higher TyG index, indicating greater insulin resistance, is associated with worse neurological outcomes in stroke patients. Early intervention targeting insulin resistance may improve clinical outcomes in ischemic stroke patients, and further research is needed to explore additional factors affecting neurological recovery.